2007
DOI: 10.1002/malq.200710014
|View full text |Cite
|
Sign up to set email alerts
|

Computing the topological entropy of shifts

Abstract: Key words Shift dynamical systems, topological entropy, type-2 computability, labeled digraphs. MSC (2000) 37B10, 37B40, 03F60 Different characterizations of classes of shift dynamical systems via labeled digraphs, languages, and sets of forbidden words are investigated. The corresponding naming systems are analyzed according to reducibility and particularly with regard to the computability of the topological entropy relative to the presented naming systems. It turns out that all examined natural representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…This kind of result brings to the field of computability questions traditionally related to dynamical systems [29]. In particular, these include deriving necessary conditions for universality [18], computability of entropy [32], [54], [27], [26] [55], and understanding the "edge of chaos [35]." Also along this line, some work has been done concerning computability of dynamical systems seen from a statistical perspective [30], [21].…”
Section: Description Of Resultsmentioning
confidence: 99%
“…This kind of result brings to the field of computability questions traditionally related to dynamical systems [29]. In particular, these include deriving necessary conditions for universality [18], computability of entropy [32], [54], [27], [26] [55], and understanding the "edge of chaos [35]." Also along this line, some work has been done concerning computability of dynamical systems seen from a statistical perspective [30], [21].…”
Section: Description Of Resultsmentioning
confidence: 99%
“…In [13] it was shown that a corresponding machine does not exist computing the topological entropy. Since the topological entropy is the topological pressure for the null function, there is no such machine computing the topological pressure.…”
Section: Theorem 37 Let X Be An M -Step Shift Of Finite Type N ≥ M mentioning
confidence: 97%
“…Next, Equation (2) gives T n v,u > 0 iff χ A * (X) (vu) = 1. Hence there is an algorithm computing the irreducible components of the transfer matrix, as shown in [13]. Furthermore, the characteristic polynomial of a matrix is computable with respect to a name of the matrix as input.…”
Section: Theorem 37 Let X Be An M -Step Shift Of Finite Type N ≥ M mentioning
confidence: 99%
See 1 more Smart Citation
“…For symbolic dynamical systems more general than the β-shifts, progress has been made recently in finding good classifications of what computational properties of their languages are needed to ensure computability of topological invariants, especially the topological entropy [32,35,14,13]. However, for β-shifts, not much is known when the shifts are no longer assumed to be sofic, bar some very interesting, but little known, results by Johnson [17].…”
Section: Examplementioning
confidence: 99%